2019
DOI: 10.7567/1882-0786/ab103e
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics of lattice distortion introduction and lattice relaxation at the surface of thermally-oxidized 4H-SiC (0001)

Abstract: The kinetics of lattice distortion introduction and lattice relaxation at the surface of thermally-oxidized 4H-SiC (0001) were investigated. Our results suggested that lattice distortion introduction and lattice relaxation seem to follow zeroth and second order rate laws, respectively. The obtained activation energy of ∼3.9 eV for lattice distortion introduction and ∼1 eV for its relaxation indicate that the lattice distortion is determined by a bond rearrangement or movement process with a relatively low acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…Different from Ar-implanted samples, the lattice relaxation of thermally-oxidized sample seems to follow second order rate law, since we found that inverse of D (D −1 ) was linearly correlated to annealing time. 10) Figure 4(c) shows the annealing temperature dependence of k relaxation of thermally-oxidized 4H-SiC samples, where the activation energy was estimated to be 1 ± 0.01 eV, which is larger than the one for Ar-implanted samples. Considering the observed activation energy and the fact that the invasion of oxygen into the surface region of thermally-oxidized 4H-SiC was physically detected using thermal desorption spectroscopy, 10) it would be reasonable to be attributed to the movement of invading oxygen into 4H-SiC lattice to form Si-O-C structure and/or formation of CO to be emitted out, [27][28][29] as already indicated in our previous work.…”
mentioning
confidence: 87%
See 4 more Smart Citations
“…Different from Ar-implanted samples, the lattice relaxation of thermally-oxidized sample seems to follow second order rate law, since we found that inverse of D (D −1 ) was linearly correlated to annealing time. 10) Figure 4(c) shows the annealing temperature dependence of k relaxation of thermally-oxidized 4H-SiC samples, where the activation energy was estimated to be 1 ± 0.01 eV, which is larger than the one for Ar-implanted samples. Considering the observed activation energy and the fact that the invasion of oxygen into the surface region of thermally-oxidized 4H-SiC was physically detected using thermal desorption spectroscopy, 10) it would be reasonable to be attributed to the movement of invading oxygen into 4H-SiC lattice to form Si-O-C structure and/or formation of CO to be emitted out, [27][28][29] as already indicated in our previous work.…”
mentioning
confidence: 87%
“…7) In our previous work, we have already reported thermal oxidation-induced lattice distortion locally at the surface region of 4H-SiC caused by the formation of the SiO 2 /4H-SiC interface. 8,9) The byproducts that remain at the 4H-SiC surface after oxidation was considered as one of the possible origins based on the detailed study of the kinetics of lattice distortion and relaxation processes, 10) even though the mechanisms of introduction of such significant distortion have not yet been clarified.…”
mentioning
confidence: 99%
See 3 more Smart Citations